Pengaruh Latihan Plyometric Knee Tuck Jump Terhadap Kecepatan Tendangan Mawashi Geri Pada Khensi Shorinji Kempo Dojo Kota Gorontalo - Zulkifli Lamusu; Anggita Harmain (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine the extent of the influence of plyometric knee tuck jump exercises on the speed of mawashi geri kicks among Shorinji Kempo athletes at the Gorontalo City dojo. The method used in this research is a quantitative approach with an experimental research design. The population in this study consisted of 35 individuals, while the sample included 12 active participants who are athletes. The sampling technique applied was purposive sampling. Data analysis was conducted using a T-test with a significance level of 0.05. The results of the study indicate a significant effect of plyometric knee tuck jump exercises on the speed of mawashi geri kicks among Shorinji Kempo athletes. In conclusion, this research demonstrates that plyometric knee tuck jump exercises can influence the speed of mawashi geri kicks at the Shorinji Kempo dojo in Gorontalo City.